Mova i stilʹ ukraïnskih narodnih dum: oznaki maskulinolektu - Becenko, Tetâna (Stylistyka, 2004)
Clause is devoted to the proof of that indisputable fact supported by the historical validity, that thoughts belong to creation of the man ’s genius. Researches are carried out on the basis of the analysis of a language material which, according to linguists, is characterized by sexual marks. The arguments resulted in the publication are based on the distinctions revealed by the scientist-linguists in word usage of men and women. The idea on complexity of such researches and ambiguity of received results expresses also. The further and profound search of ways and the methods connected to the decision of problems of a floor and style is offered.